ROLE-PLAY AS A DRAMA TECHNIQUE: ASSESSING ITS EFFECTS ON IRAQI EFL STUDENTS’ SPEAKING ANXIETY AND SPEAKING ABILITY - AL-Zurfi, Ali; Hadi, Benin Abdel; Salman, Tabarak (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigated the impact of role-play techniques on speaking anxiety and speaking ability among Iraqi EFL learners. Method: Using a mixed-methods design, 60 undergraduates were divided into experimental (role-play) and control (traditional instruction) groups. Results: Quantitative results significantly reduced speaking anxiety (mean change = -8.31, p < 0.001). They improved speaking scores (mean change = 5.17, p < 0.001) for the experimental group, while qualitative data highlighted enhanced confidence and fluency. Challenges included peer pressure and feedback needs. Novelty: The findings are supporting role-play as an effective pedagogical tool. Recommendations include structured feedback and diversified scenarios to maximize benefits.